Dialog Lintas Agama dan Upaya Deradikalisasi - Achmad Zainul Arifin; Asyhad Abdillah Rosyid; M Thoriqul Huda (UIN Sunan Kalijaga Yogyakarta, 2022)
Heterogeneous religious life requires mutual awareness to respect and maintain tolerance in religious life. Dialogue is one of the efforts to strengthen tolerance in religious communities. Inter-religious dialogue also plays a role in preventing the entry of radical ideas into people's mindsets and behavior. This study examines the role of dialogue in building tolerance and counteracting radicalism in the work program of FKUB Mojokerto. The results show that dialogue plays a full role in building narratives and inclusive behavior in religion, it acts as a bulwark of resistance against the entry of radical understanding in religious communities.